(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Range of diseases from bacterial infections to cancer, the global rise in drug resistance is a formidable challenge. Multidrug resistant infections, which complicate treatment and raise mortality, have been emerging from bacterial pathogens that increasingly evolve ways to evade antibiotics. But this forms of resistance is not unique to infectious diseases—cancer cells learn to resist chemotherapeutic agents and standards treatments become less effective over time. But the mechanisms of resistance vary and are often based on genetic mutations, or pumping the drug out by efflux pumps, or adaptive metabolic changes that are meant to allow cells to live during exposure to drug. Furthermore, over prescription, incorrect dosing and poor infection control practices are compounds that worsen the scenario by increasing drug resistance to available therapies. With resistance spreading, novel therapeutic strategies, including precision medicine approaches, combination therapies, and the creation of therapies directed at these resistance mechanisms, are needed. To address drug resistance across disease types will require a collaborative, interdisciplinary approach that combines microbiology, oncology, pharmacology and public health.